2014
DOI: 10.1371/journal.pone.0114696
|View full text |Cite
|
Sign up to set email alerts
|

CASP8 SNP D302H (rs1045485) Is Associated with Worse Survival in MYCN-Amplified Neuroblastoma Patients

Abstract: BackgroundNeuroblastoma is a pediatric cancer that exhibits a wide clinical spectrum ranging from spontaneous regression in low-risk patients to fatal disease in high-risk patients. The identification of single nucleotide polymorphisms (SNPs) may help explain the heterogeneity of neuroblastoma and assist in identifying patients at higher risk for poor survival. SNPs in the TP53 pathway are of special importance, as several studies have reported associations between TP53 pathway SNPs and cancer. Of note, less t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 35 publications
1
22
0
1
Order By: Relevance
“…Among the polymorphic sites of CASP8, rs3834129 (-652, 6N ins/del) polymorphism, a six-nucleotide insertion (I)/deletion (D) variant, has been functionally identified to lead to down-regulation of the mRNA of CASP8 (18). Caspase-8 single nucleotide polymorphisms are reported to be genomic markers for the prediction of the personal risk for several types of cancers such as that of the digestive tract (19,20), breast (21)(22)(23), prostate (24), lung (25) and bladder (26), and neuroblastoma (27). Little is known about the role of CASP8 polymorphisms in oral cancer.…”
mentioning
confidence: 99%
“…Among the polymorphic sites of CASP8, rs3834129 (-652, 6N ins/del) polymorphism, a six-nucleotide insertion (I)/deletion (D) variant, has been functionally identified to lead to down-regulation of the mRNA of CASP8 (18). Caspase-8 single nucleotide polymorphisms are reported to be genomic markers for the prediction of the personal risk for several types of cancers such as that of the digestive tract (19,20), breast (21)(22)(23), prostate (24), lung (25) and bladder (26), and neuroblastoma (27). Little is known about the role of CASP8 polymorphisms in oral cancer.…”
mentioning
confidence: 99%
“…However, our data are in accordance with a recent pilot investigation, reporting, albeit with borderline statistical significance, a negative prognostic impact of the CASP8 -652 6N Del allele for colorectal cancer patients [ 19 ]. Complementarily, in a very recent approach, CASP8 302His was associated with worse overall and event-free survival in patients with MYCN-amplified neuroblastoma tumors [ 18 ]. Apoptosis, with caspase 8 as one of its key regulators, is not only involved in AICD of antitumor T lymphocytes, but also constitutes an important defense mechanism against hyperproliferation and malignancy, which can be induced by e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Beside the extensively studied role of the above mentioned caspase 8 polymorphisms in cancer susceptibility, recent approaches also started to investigate, whether these polymorphisms also influence the outcome of cancer in patients with already existing disease. In this context, recent pilot investigations reported a negative prognostic impact for the CASP8 -652 Del allele or the CASP8 302His allele for patients with colon cancer or neuroblastoma, respectively [ 18 , 19 ]. However, although breast cancer was primarily adressed by recent CASP8 -652 6N Del and CASP8 Asp302His susceptibility studies, surprisingly, prognostic relevance of these caspase 8 polymorphisms has not been investigated in breast cancer so far.…”
Section: Introductionmentioning
confidence: 99%
“…18,37 CASP8 polymorphisms were related to many cancers, including lung cancer and neuroblastoma. [38][39][40] Son et al found that CASP8 IVS12-19 GG genotype was significantly increased for the risk of small cell carcinoma (SmCC), rather than IVS12-19 AA and IVS12-19 GA genotypes. 38 However, this is the first time that rs3769821 and rs1045494 of CASP8 was reported to be associated with lung adenocarcinoma OS in our study, and the patients with AA genotype of rs3769821 had 6.7 months longer OS than patients with GG or AG genotypes (p D 0.007).…”
Section: Immortality Of Injured Cells and Induction Of Various Cancersmentioning
confidence: 99%